Leukemic lymphoblasts, a novel expression site of coagulation factor XIII subunit A - Kiss, Flóra; Hevessy, Zsuzsanna; Veszprémi, Anikó; Katona, Éva; Kiss, Csongor; Vereb, György; Muszbek, László; Kappelmayer, János (Thrombosis and Haemostasis, 2006)
Blood coagulation factor XIII (FXIII) is a protransglutaminase circulating asa tetramer formed by two types of subunits (A2B2). The intracellular dimeric form of FXIII (A2) is present in platelets, megakaryocytes, monocytes and macrophages and has been detected in mono-and megakaryocytic leukemias. The aim of our study was to investigate FXIII-A expression in newly diagnosed B cell acute lymphoblastic leukemia (ALL) samples. We examined 47 de novo ALL cases of B cell origin by triple color labeling with flow cytometry. FXIII-A was detected by a FITC conjugated monoclonal antibody combined with CD34 and CD45 staining. In selected cases FXIII-A was investigated on slides prepared from blasts and visualized with a fluorescent microscope. In addition, blasts were studied by Western blot analysis and FXIII-A was measured by a highly sensitive ELISA method. By flow cytometry 19 samples of the 47 cases were found to be FXIII-A positive. Antigen concentration was 3.11± 1.19 fg/blast, while normal lymphoid precursors and mature lymphocytes from B-CLL did not contain FXIII-A. In the lysate of lymphoblasts that were positive by flow cytometry, a single band (82 kDa) corresponding to FXIII-A was detected on Western blots. Confocal laser scanning microscopic examination revealed the presence of FXIII-A in the cytoplasm of these lymphoblasts. This novel expression site of FXIII-A in leukemic lymphoblasts can be utilized as a diagnostic tool and may also gain functional significance in B-lineage ALL.
Keywords: Coagulation factor XIII; acute lymphoblastic leukemia; flow cytometry